COMPREHENSIVE REVIEW OF INFECTION CONTROL PRACTICES AND EVALUATING STRATEGIES, COMPLIANCE, AND IMPACT ON HEALTHCARE-ASSOCIATED INFECTIONS IN CLINICAL SETTINGS - Abdullah Moslah Hamad Alswidan, Ali Yahya Fhaed Alswedan, Abdullah Hamad Shagath Al Suliman , Ali Mosleh Hamad Al Sawadan , Saif Muslih Alsawidan, Hamad Muslih Alsawidan , Abdullah Musleh Mohammed Alswidan , Hadi Musleh Mohammed Al Suwaidan (Chelonian Research Foundation, 2022)
Implementing proper infection control guidelines is an essential step in fighting against the progress of healthcare-associated infections (HAIs) in healthcare facilities. Therefore, this review comprehensively explores each option available with deep analysis and their perspective on keeping HAIs at bay. In that way, a comprehensive study of infection control measures is being made to see if they are efficient, identify critical compliance challenges, and determine patient recoveries. Discussions on methodologies for evaluating the soundness of infection control strategies follow, along with presenting some relevant proof and advice to strengthen the infection absence initiatives. The analysis findings show the significance of multipronged efforts in infection prevention and serve as a call for continued monitoring, learning, and cooperation among stakeholders for effective HAI management. Keywords: infection management, healthcare infections, medical settings, patients' outcomes.